Peran Dukungan Sosial terhadap Career Search Efficacy dengan Moderator Future Work Self pada Mahasiswa di Kota Bandung - Gianti Gunawan; Indah Puspitasari; Meta Dwijayanthy (Syntax Literate, 2023)
One of the developmental tasks in adolescence and early adulthood is finding the right career direction. Finding a career that matches your interests and ways to actualize yourself, becomes something that needs to be explored and start in adolescence. Students also cannot be separated from the exploration process to find a career that is in line with their interests and abilities. This career exploration process is lead to career search efficacy. In addition, the student's representation of himself in the future that reflects his expectations and aspirations related to work becomes very important to have. This research wants to see the role of social support, especially from parents and peers towards career search efficacy with the moderator of future work self-students. The population of this study is students in the city of Bandung. Data analysis techniques using linear regression between social support variables and career search efficacy, with future work self variables as moderators. The results showed that parental social support and peer social support simultaneously did not contribute to the variable career self-efficacy. Partial parental social support showed no contribution to predicting career self-efficacy. Similar results also occurred in peer social support that did not significantly contribute to predicting career self-efficacy. The future work self variable does not moderate the influence between parental social support and career self-efficacy. On the other hand, the future work self variable can moderate the influence between peer social support on career self-efficacy.